TaBAS1 encoding a typical 2-Cys peroxiredoxin enhances salt tolerance in wheat - Xiao, Guilian; Zhao, Mingming; Liu, Qinghua; Zhou, Junzhi; Cheng, Zhaohui; Wang, Qiannan; Xia, Guangmin; Wang, Mengcheng (Frontiers in Plant Science, 2023)
Efficient antioxidant enzymatic system contributes to salt tolerance of plants via avoiding ROS over-accumulation. Peroxiredoxins are crucial components of the reactive oxygen species (ROS) scavenging machinery in plant cells, but whether they offer salt tolerance with potential for germplasm improvement has not been well addressed in wheat. In this work, we confirmed the role of a wheat 2-Cys peroxiredoxin gene TaBAS1 that was identified through the proteomic analysis. The seedlings of wheat overexpressing TaBAS1 had superior salt tolerance. TaBAS1 overexpression enhanced the tolerance to oxidative stress, promoted the activities of ROS scavenging enzymes, and reduced ROS accumulation under salt stress. TaBAS1 overexpression promoted the activities ROS production associated NADPH oxidase, and the inhibition of NADPH oxidase activity abolished the role of TaBAS1 in salt and oxidative tolerance. Moreover, the inhibition of NADPH-thioredoxin reductase C activity erased the performance of TaBAS1 in the tolerance to salt and oxidative stress. TaBAS1 overexpression enhanced the gain yield of wheat under salt stress but not the control condition, not imposing the trade-offs between yield and tolerance. Thus, TaBAS1 could be used for molecular breeding of wheat with superior salt tolerance.